The Influence of Product Quality, Price, and Online Customer Reviews on the Purchase Decision of MS Glow Products with Purchase Intention as an Intervening Variable - tazkia robbani, warda (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study to determine the Influence of Product Quality, Price, and Online Customer Review on Purchase Decisions of Ms Glow Products with Purchase Intention as an Intervening Variable among Ms Glow product consumers in Semarang society. The sample in this study consisted of 96 respondents, selected using non-probability sampling method. The research data were processed using Smart PLS 4.0. The results of the study are as follows: (1) Product quality has no influence on purchase decisions, (2) Price has a positive and significant influence on purchase decisions, (3) Online customer reviews have no influence on purchase decisions, (4) Product quality has a positive and significant influence on purchase intention, (5) Price has a positive and significant influence on purchase intention, (6) Online customer reviews have a positive and significant influence on purchase decisions, (7) Purchase intention has a positive and significant influence on purchase decisions, (8) Product quality has a positive and significant influence on purchase decisions through purchase intention, (9) Price has a positive and significant influence on purchase decisions through purchase intention, (10) Online customer reviews influence purchase decisions through purchase intention.